Overcoming Bullying through Character Learning: Building Positive Personality in Students - Gamar Abdullah; Maria Purnama Nduru; Mumu Muzayyin Maq; Muh. Safar; Fauzi Aldina (Edumaspul: Jurnal Pendidikan, 2024)
Bullying has become a disturbing problem in the school environment, with detrimental impacts on victims and the learning environment as a whole. To overcome this problem, an integrated and effective approach is needed, one of which is through character learning in schools. This research uses a qualitative approach with literature study to understand the relationship between character learning and bullying prevention. Through identification of problem topics, literature searches, analysis, and selection of the latest literature, this research aims to explore the effectiveness of character learning in overcoming bullying, understanding appropriate core values, self-strengthening, and managing students' emotions, short and long term impacts of bullying, as well as the role of bystander intervention in encouraging student intervention in bullying situations. The research results show that character education plays an important role in reducing bullying incidents, by strengthening values such as empathy, justice, respect for differences, responsibility and courage. The short and long term impacts of bullying on students include stress, decreased emotional well-being, impaired concentration, mental health problems and low self-esteem. The short and long term implications of bullying include hindered personal development, increased health care costs, and lost productivity. Prevention and intervention strategies include education and awareness, anti- bullying policies, emotional and mental health support, and development of social skills and resilience. Bystander intervention is also important in encouraging students to intervene and fight bullying. This research provides a comprehensive picture of the importance of character learning in overcoming bullying in the school environment and presents practical implications and recommendations for the future.